CIAT Values and principles. Episode #1 - International Center for Tropical Agriculture (2014)
CIAT has just launched its Strategy 2014--2020. With the aim to meet our goals and objectives, we have decided to further strengthen our core values, which are based on a set of shared ethical principles, leading us to work together in teams and with partners in a pragmatic and efficient way, to achieve high-quality research, which is innovative and impact oriented. Here is a small example of how we together are the Change that strengthens science.